1363Just a flu? Comparing COVID-19 and influenza mortality. (2nd September 2021) - Muscatello, David; McIntyre, Peter
Abstract: Background: Benchmarks are needed for assessing the severity of the COVID-19 pandemic. However, comparisons can be misleading unless marked differences in age-specific mortality and differences in population age structure are considered. Methods: Using COVID-19 death rates for New York City as at 2 June 2020, we used indirect age standardization to estimate standardized mortality ratios (SMR) for the first winter waves of the 1918 and 2009 influenza pandemics and the severe 2017-2018 influenza season in the United States (US). Data were obtained from published statistics. Results: After adjusting for age, New York City's death rate during the 1918 winter influenza pandemic wave was 6.7 times higher overall compared with the first wave of COVID-19 in 2020. New York City's first wave COVID-19 death rate was an estimated 59 times higher than that of the 2009 US influenza pandemic, and 14 times higher than that of the severe 2017-2018 influenza season. In < 45 year-olds, the 1918 influenza death rate was 42 times higher than COVID-19 in 2020. In ≥ 65 year-olds, compared with the 2009 pandemic, the COVID-19 death rate was 320 times higher, while in children it was one half. Conclusions: The 1918 pandemic was more deadly than COVID-19, which was, in turn, far more deadly than both the 2009 influenza pandemic and severe seasonal influenza. Age-specific mortality differences should be considered in decisions on COVID-19 vaccination strategies. Key messages: Fundamental epidemiological methods remain valuable for modern epidemic risk assessment. COVID-19 is not just a 'flu'.